Metal-complexed monoazo dyes as sustainable permanent hair dye alternatives—Toxicological and durability properties. (January 2022) - Williams, Tova N.; Vacchi, Francine I.; dos Santos, Amanda; Aragão Umbuzeiro, Gisela de; Freeman, Harold S.
Abstract: As a new approach to permanent/oxidative hair dyes, we demonstrated that certain monoazo dyes containing substituents that enable diffusion into hair fibers and subsequent chelation/complexation using benign metal ions (Al 3+ and Fe 3+ ), rather than a harsh oxidant and strong alkali, merit consideration in this application area. This is important, because billions of individuals worldwide color their hair using permanent hair dye products that can contain aromatic amines and phenols that display genotoxicity and/or skin sensitization (e.g., para -phenylenediamine, PPD). Herein, our work is extended to an examination of the toxicological properties and durability of metallizable monoazo dyes, in comparison to a commercially used permanent hair dye product. Results from the Salmonella /microsome mutagenicity assay and from acute toxicity tests using aquatic test organisms ( Daphnia similis, 48-h and Parhyale hawaiensis, 96-h) indicated that the proposed dyes were significantly less toxic than the top-eight permanent hair dye precursors utilized annually. Regarding durability, monoazo dye chelation in situ led to a higher degree of resistance to removal by washing than a commercial permanent hair dye. Taken together, these results further demonstrate the potential of the dyes as sustainable alternatives to conventional permanent hair dyes. Graphical abstract: Image 1 Highlights: The toxicological and durability properties of monoazo dyes were established. Ames test results showed monoarylide and arylazonaphthol dyes were not mutagenic. The aquatic toxicity of all dyes was lower than permanent hair dye precursors. Arylazonaphthol dye was more wash resistant than a permanent hair dye standard.